UPAYA KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA PENCABULAN ANAK - Widi Mandala Putra, Wayan; Wairocana, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014)
Scientific writing is about the efforts made by the police in conducting criminal offense prevention of child molestation in the city of Denpasar. The scientific literature using this type of empirical research with empirical judicial approach. The problem that arises is reviewed and assessed based on theories or legal provisions that govern them and then attributed to the fact that actually exist in the community. The type of approach is the approach used law legislation and approach the facts. The results showed that the reduction of child molestation is done by repressive efforts, prosecution of perpetrators of child abuse according to law. Further preventive measures that are operational conducted raids porn videos and preventive counseling is counseling done with school. So the conclusion here of police efforts in tackling the crime of child molestation made by two repressive efforts and the efforts of preventive measures.
Keywords: sexual abuse, Children, Preventive Efforts, Repressive efforts